Water use pattern and yield response of groundnut (Arachis hypogaea L.) in semi-arid areas of India - DAS, H. P.; SAMUI , R. P.; SATOSKAR, M. V. (MAUSAM, 1998)
Groundnut, an important food legume, is extensively grown in semi-arid regions of India. Water use, water use efficiency and yield response of groundnut grown at three locations, viz., Bellary, Rahuri and Anand during kharif season have been studied for 3 to 5 years. Reduction in pod yield due to moisture stress was found greatest at Rahuri, where a relatively short duration crop was grown in a clayey soil. Total water use was highest at Anand, followed by Bellary and Rahuri. The water use was 660, 460 and 410 mm respectively. At all locations evapotranspiration by the crop was maximal at peg formation to pod development stage of crop growth. The water use efficiency was highest at Bellary followed by Anand and Rahuri. The relative evapotranspiration ratio ETc/ETo for the entire growing season was 0.97, 0.63 and 0.92 at Anand, Bellary and Rahuri respectively. Pod yield showed good correspondence with total water use.